2003
DOI: 10.1111/j.1752-1688.2003.tb04422.x
|View full text |Cite
|
Sign up to set email alerts
|

MARSH DEVELOPMENT AT RESTORATION SITES ON THE WHITE MOUNTAIN APACHE RESERVATION, ARIZONA1

Abstract: To prioritize sites for riparian restoration, resource managers need to understand how recovery processes vary within landscapes. Complex relationships between watershed conditions and riparian development make it difficult to predict the outcomes of restoration treatments in the semiarid Southwest. Large floods in 1993 scoured riparian areas in the Carrizo watershed on the White Mountain Apache Reservation in east‐central Arizona. We evaluated recovery at three of these sites using repeated photographs and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Several studies found that riparian vegetation metrics varied across seasons and years, making it difficult to detect change, particularly over short time periods (Long et al. 2003; Laine et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies found that riparian vegetation metrics varied across seasons and years, making it difficult to detect change, particularly over short time periods (Long et al. 2003; Laine et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cook (2003) found significantly higher periphyton in nonfenced reaches than in fenced reaches, with lower levels attributed to higher plant biomass just 1-2 years after exclusion implementation and changes in stream shading due to increases in riparian vegetation; however, our review included no other studies that measured periphyton. Results were mixed for aquatic vegetation cover, indicating that livestock grazing reduction does not lead to consistent changes in aquatic vegetation cover (2 of 4 studies reported decreases, with 1 being significant; 1 of 4 studies reported no change; Thibault et al 1999;Long et al 2003;Scrimgeour and Kendall 2003;Herbst et al 2012).…”
Section: Effectiveness Of Livestock Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Er bestaan veel toepassingen in de literatuur: voor het detecteren van verschillen in soortendensiteit in graslandgemeenschappen onder verschillende beheervormen (Lörentzen et al, 2008), om verschillen in bodemkenmerken ten gevolge van begrazing te onderzoeken (Muscha & Hild, 2006), om vegetatieveranderingen langs begrazingsgradiënten met een verschillende begrazingsdruk te vergelijken (Hoshino et al, 2009), om wegbermgemeenschappen langs omgevingsgradiënten te beschrijven (Arévalo et al, 2005;Karim & Mallik, 2008), bij zonering van oevers van stilstaande waters en kustecosystemen (Keddy 1984;Steinhardt 2009), voor de beschrijving van successiegradiënten (Jerling, 1983), ter evaluatie van het herstel van oevergemeenschappen (Long et al, 2003).…”
Section: Lijntransectenunclassified
“…Planting of wet meadow vegetation without corresponding restoration of hydrologic process may lead to limited recovery of sensitive, wetland obligates such as Carex , and to the invasion of woody plants (Meyer et al 2010). Where emergent wetlands have been reduced due to intense, scouring floods, recovery can be rapid where fine, silty sediment and surface water are fostered by geologic and geomorphic characteristics that occur commonly in low-gradient valley bottoms (Long et al 2003).…”
Section: Riparian Herbaceous Wetlands: Historical Role and Ecologicalmentioning
confidence: 99%